2015
DOI: 10.1002/jcb.25458
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Ribosomal Protein S6 at Nucleolus Is Cell Cycle‐Controlled and Its Function in Pre‐rRNA Processing Is Phosphorylation Dependent

Abstract: Ribosomal protein S6 (rpS6) has long been regarded as one of the primary r-proteins that functions in the early stage of 40S subunit assembly, but its actual role is still obscure. The correct forming of 18S rRNA is a key step in the nuclear synthesis of 40S subunit. In this study, we demonstrate that rpS6 participates in the processing of 30S pre-rRNA to 18S rRNA only when its C-terminal five serines are phosphorylated, however, the process of entering the nucleus and then targeting the nucleolus does not dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The rationale for this assay is based on the observation that defects if biogenesis pathway can cause ribosomal subunit export defects 80, 81 . Rps6 is an early assembling 40S subunit ribosomal protein 8284 , allowing us to score early defects in 40S synthesis. Indeed, we found an accumulation of RPS6 in the nucleus in Pex5 RNAi oenocytes, after normalized to total intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for this assay is based on the observation that defects if biogenesis pathway can cause ribosomal subunit export defects 80, 81 . Rps6 is an early assembling 40S subunit ribosomal protein 8284 , allowing us to score early defects in 40S synthesis. Indeed, we found an accumulation of RPS6 in the nucleus in Pex5 RNAi oenocytes, after normalized to total intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic accumulation of RPS6 in the nucleolus, in accordance with the cell cycle, has been reported; it starts in the S phase, culminates in the G 2 phase, and diminishes in the M phase with the disintegration of the nucleoli [ 327 ]. In addition, mammalian RPS6 is dephosphorylated upon heat shock [ 328 , 329 ].…”
Section: Regulation Of Rps6mentioning
confidence: 99%
“…However, the hepatic hypertrophy but not hyperplasia in fasted animals in response to nutrients was not blocked by the absence of RPS6. A recent study has demonstrated that p-RPS6 is involved in the endonuclease processing of 30S pre-rRNAs in the nucleolus [ 327 ]. The splicing of 30S pre-rRNAs was only mediated by fully phosphorylated RPS6 in the C-terminal five serine residues.…”
Section: Functions Of Rps6mentioning
confidence: 99%
“…Activated p53 then transactivates its downstream targets to induce growth arrest and apoptosis to block tumorigenesis. (Adilakshmi and Laine, 2002;Bai et al, 2014;Barlow et al, 2010a;He and Sun, 2007;Jang et al, 2012a;Jeon et al, 2008;Khanna et al, 2003;Li et al, 2010;Naora et al, 1998;Neumann and Krawinkel, 1997;Russo et al, 2013;Takagi et al, 2005;Wu et al, 2012;Yang et al, 2012;Zhu et al, 2009) Cell cycle S3, S5, S6, S7, S14, S15, S19, S20, S25, S26, S27, S27L, S27a, L3, L5, L6, L7, L11, L13, L23, L26, L31, L34, L37, L41 (Cui et al, 2014;Daftuar et al, 2013;Dai et al, , 2007bGao et al, 2013;Gou et al, 2010;Iadevaia et al, 2010;Kobayashi et al, 2006;Maruyama et al, 2014;Matragkou et al, 2008;Moorthamer and Chaudhuri, 1999;Neumann and Krawinkel, 1997;Russo et al, 2013;Sun et al, 2011;Takagi et al, 2005;Wang et al, 2011a;Wanzel et al, 2008;Xiong et al, 2011;Zhang et al, 2013Zhang et al, , 2015Zhou et al, 2013a) Cell proliferation S6, S9, S13, S14, S15a, S24, S27, L6, L8, L11, L15, L17, L26, L29, L31, L34, L36a (Dai et al, 2007a;Gou et al, 2010Kim et al, 2004;Li et al, 2010…”
Section: Apoptosismentioning
confidence: 99%